2017
DOI: 10.1177/1077558717737841
|View full text |Cite
|
Sign up to set email alerts
|

Care Transformation Strategies and Approaches of Accountable Care Organizations

Abstract: Although accountable care organizations (ACOs) proliferate, little is known about the activities and strategies ACOs are pursuing to meet goals of reducing costs and improving quality. We use semistructured interviews with executives at 16 ACOs to understand ACO approaches. We identified two overarching ACO approaches to changing clinical care: a practice-based transformation approach, working to overhaul care processes and teams from the inside out; and an overlay approach, where ACO activities were centraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The ACO-participating physicians may be more focused on effectively managing chronic illnesses and better equipped to do so. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The ACO-participating physicians may be more focused on effectively managing chronic illnesses and better equipped to do so. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Social resiliency and social equality can lead to the benefits of lower infection rates and associated treatment costs, increasing health care access and risk reduction strategies in order to improve livelihood and productivity in countries that are prone to infectious diseases and pandemic threats (3,7,25,30,35).…”
Section: Strengthening Acceptable and Effective Intervention Packagesmentioning
confidence: 99%
“…Communities can become less engaged as disease incidence declines, and consequently less involved in control activities, or start actively refusing vaccination. Once elimination and eradication have been achieved, returns on investment, health and economic benefits are potentially infinite (4,10,35).…”
Section: Integration Of Outcome-based and Sustainable Social Equalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Research has primarily relied on data gathered from surveys and interviews of ACO executives and physician leaders. [12][13][14][15][16] A recent national survey of primary care physicians (PCPs) and internal medicine specialists during the early ACO experience (2014-2015) found that Medicare ACOs had limited success engaging physicians in decision-making, awareness of ACO incentives, or changing care delivery. 17 However, there are no data on ACO engagement of other physician specialists (who make an outsized contribution to total spending), physician assistants, or advanced practice nurses.…”
Section: Introductionmentioning
confidence: 99%